Fibrino(geno)lytic Properties of Purified Hementerin, a Metalloproteinase from the Leech Haementeria depressa - Chudzinski-Tavassi, Ana Marisa; Kelen, Eva Maria A.; Rosa, Ana Paula de Paula; Loyau, Stephane; Sampaio, Claudio A. M.; Bon, Cassian; Anglés-Cano, Eduardo (Thrombosis and Haemostasis, 1998)
The fibrino(geno)lytic protein designated hementerin contained in crude extracts of the salivary complex of Haementeria depressa leeches was purified to apparent homogeneity by gel filtration, ion exchange chromatography and preparative SDS-PAGE. It is a single-chain 80 kDa, PhMeSO2F-resistant, calcium-dependent, metalloproteinase, which specifically degrades fibrin(ogen) through a plasminogen-independent pathway. The amino terminal sequence of 8 residues shows 80% similarity with hementin, another fibrino(geno)lytic protein purified from Haementeria ghilianii leeches. However, their activities differ somewhat in terms of kinetics and with regard to the structure of the fibrin(ogen) fragments they may produce. Cleavage by hementerin of fibrinogen Aα, γ and Bβ chains, in that order, produces 270 kDa to 67 kDa fragments which differ from those produced by plasmin. Hementerin was also able to degrade cross-linked fibrin although at a lower rate as compared to fibrinogen. In conclusion, hementerin is a plasminogen-independent fibrino(geno)lytic metalloproteinase that degrades fibrinogen faster than fibrin, prevents blood coagulation and destroys fibrin clots in vitro.